Efektivitas Komunikasi Dalam Meningkatkan Kinerja Karyawan - Asmawati Halilah Damanik; Eve Ida Malau; Richard Berlien (Jurnal Akuntansi Dan Manajemen Indonesia (JAMIN), 2021)
Every individual in work not only wants a salary and achievement, but work is a fulfillment of the need for social interaction. Teachers who have friendly and supportive co-workers will lead them to good work results as well. The success of school communication can be interpreted as the effectiveness of communication between the principal and his subordinates (teachers). The purpose of this study was to determine the communication between the principal and the teacher that occurred at SMA Muhammadiyah 7 Serbalawan. Data collection techniques by conducting observations, interviews, and documentation. The analysis technique in this study is a qualitative descriptive analysis technique with the approach of Miles and Huberman. The result of the analysis is that communication between the principal and the teacher is an action that must be maintained properly in order to improve the quality of the relationship between the principal and the teacher. Broadly speaking, the communication relationship between the two is good and needs to be maintained in order to remain harmonious and create an atmosphere of modesty and peace.